Peran Guru Bimbingan Konseling Dalam Implementasi Kurikulum Merdeka Dan Pencapaian Profil Pelajar Pancasila - Datuti, Sri; Lede, Yohanes Umbu (Varied Knowledge Journal, 2024)
This study discusses the role of counseling guidance (BK) teachers in the implementation of the Independent Curriculum developed by the Ministry of Education, Culture, Research and Technology (Kemendikbudristek) as an effort to restore learning due to the pandemic. The Independent Curriculum was introduced as an additional option for education units in learning recovery during the period 2022-2024, with a policy evaluation to be conducted in 2024. One of the main objectives of this curriculum development is to shape students with a Pancasilais profile, in line with national education goals. In this context, counseling teachers have a crucial role as agents of change, prevention, counselors, consultants, coordinators, assessors, and career developers. This research is a literature study that focuses on the importance of the role of counseling teachers in supporting the implementation of the Independent Curriculum to achieve student profiles based on Pancasila values. The results show that optimizing the role of counseling teachers is needed in the successful implementation of this curriculum towards the formation of a Pancasilais generation.